In Hip hop Time: Music, Memory and Social Change in Urban Senegal - Harris, Corey (International Library of African Music, 2020)
pages: 164-168
Keywords: Book reviews; Hip-hop; Social change; Collective memory; Cultural Memory; Senegal; Urban Culture; African Music